Competitiveness of the Southeast European countries in the conditions of the globalization - Jelena Živković (Economic Themes, 2021)
Globalization is a process often identified with the economic integration of countries, the creation of a single market while neglecting other aspects of globalization. Besides its economic dimension, The KOF index of globalization includes the social and political dimensions. One of the questions is how the countries manage to strengthen their competitive position in the international market in the age of globalization. Is it challenging to maintain a stable competitive position in the conditions of greater connection of countries and in what form? For this reason, the paper deals with the change of the Global Competitiveness Index, a renowned measure of the competitiveness of national economies according to the methodology of the World Economic Forum, under the influence of increased economic globalization of Southeast European countries. It also estimates the impact of globalization, or its economic, social and political dimension on the economic growth of Southeast European countries, which is one of the requirements for successful positioning on the international economic scene.
Keywords: F60; F63; O11; 330; competitiveness; economic growth; globalization; economic globalization; Southeast Europe; KOF Globalization Index; Global Competitiveness Index